O perfil da cultura política da cidade do Rio Grande em 2008 - Pinto, Paulo Sérgio Mansija (2009)
The Culture politics according to Almond and Verba (1963) is to the orientations specifically politics, the attitudes with respect to the system politician, its diverse parts and the paper of the citizen in the public life. To the measure that if explicit the standards of distribution of orientation for the action politics, the Culture Politics helps to bind individual trends to the characteristics of a system. In this scope it was objectified to investigate the culture politics of the riograndino citizen, breaking of the hypothesis of the culture politics of the riograndino citizen to show personalist and pragmatic, marked for phenomena as the discredit and the diffidence in relation to the politics and the politicians, beyond a strong feeling of inefficacy politics. Such phenomena would disclose to a culture fragmented and skeptical politics. It will be used as the quantitative research arrives in a set methodological, constituted of a sample of conglomerates (tax sector) of 400 voters of the urban area. Randomly it was defined, in a universe of (xnº) sectors of the city, (xnº) of sectors to search. Stipulating 10 questionnaires to the minimum sector, 15 to intermediary and 20 to the maximum. Survey composes in 24 questions for instrument form, searched to investigate 0 variable related to the partner-demographic characteristics, interest for politics, partisan preference, decision of the vote, and factors in the electoral choice, vote for mayor and councilmen, confidence in the institutions politics and participation politics of the citizens. The data harvested for the empirical research had corroborated the hypothesis; however, the research displayed peculiarities of the system local politician not foreseen. The biggest obstacle to the research is the complexity of if apprehending the reality, demanding research in times thus alternated to prove the regularity of the behavior politician, therefore the sounding of a moment.